Climate change in southwestern British Columbia: Extending the boundaries of earth science - Clague, John; Turner, Robert (Geoscience Canada, 2000)
Summary Humans are altering the composition of the atmosphere, causing climate to change. Scientists predict that by the middle of the 21st century, average global temperatures will be several degrees warmer than today. The change in climate will be the largest and most rapid of thelast 10,000 years and will have profound effect on our lives and the ecosystems that support us. This paper describes a new, graphics-rich, colourful poster dealing with climate change in southwestern British Columbia. The poster, which is being used as a template for six other regional climate change posters in Canada, discusses the science of climate change, possible impacts of climate change over the next 50 years in south-western British Columbia, and the challenge of dealing with this issue. The target audience for the poster is students in grades 10-12, colleges and universities, their teachers, and the educated general public. In preparing the poster, we were guided by the principle that to educate ist o engage critical thought.